Eksistensi Sekolah Pesisi Juang Dalam Memenuhi Hak Pendidikan Bagi Anak-Anak Pesisir Di Lingkungan Bintaro Kecamatan Ampenan Kota Mataram - Prisma Akbar, Lalu; Sumardi, Lalu; Alqadri, Bagdawansyah; Nurmalisa, Yunisca (Mataram University, 2024)
This research explores the role of Sekolah Pesisi Juang in fulfilling the educational rights of coastal children in Bintaro, Ampenan, Mataram. The research focuses on the school's contribution to enhancing learning motivation, literacy, and practical skills of the children, who face various social and economic challenges. Using a qualitative case study approach, data were collected through interviews, observations, and document analysis. The findings show that the school has implemented various educational programs, including Early Childhood Education (PAUD), Pojok Baca, Pojok Kreasi, and additional classes that have successfully helped meet the educational needs of these children. The study also highlights supporting and inhibiting factors in the school's efforts and presents strategies for overcoming obstacles.